2015
DOI: 10.5966/sctm.2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Endothelial Colony-Forming Cells Overexpressing Integrin β1 Augments Angiogenesis in Ischemic Legs

Abstract: When injected directly into ischemic tissue in patients with peripheral artery disease, the reparative capacity of endothelial progenitor cells (EPCs) appears to be limited by their poor survival. We, therefore, attempted to improve the survival of transplanted EPCs through intravenous injection and gene modification. We anticipated that overexpression of integrin b 1 will enable injected EPCs to home to ischemic tissue, which abundantly express extracellular matrix proteins, the ligands for integrins. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
(51 reference statements)
1
37
0
Order By: Relevance
“…However, lentiviral vector gene delivery of a constitutively active Akt1 mutant was able to rescue the pro-angiogenic activity of SA men-derived ECFCs by recruiting eNOS, thereby restoring their therapeutic outcome in vivo [ 229 ]. A slightly different approach consisted in forcing ECFCs to overexpress integrin β1 [ 230 ], which promotes ECFC binding to extracellular matrix proteins in ischemic tissues [ 231 ] and further exerts independent angiogenic effects [ 232 ]. ECFCs were engineered with a lentivirus encoding for murine integrin β1 and injected, either locally or intravenously, in a murine model of hindlimb ischemia [ 230 ].…”
Section: Genetic Manipulation Of Pro-angiogenic Signaling Pathwaysmentioning
confidence: 99%
“…However, lentiviral vector gene delivery of a constitutively active Akt1 mutant was able to rescue the pro-angiogenic activity of SA men-derived ECFCs by recruiting eNOS, thereby restoring their therapeutic outcome in vivo [ 229 ]. A slightly different approach consisted in forcing ECFCs to overexpress integrin β1 [ 230 ], which promotes ECFC binding to extracellular matrix proteins in ischemic tissues [ 231 ] and further exerts independent angiogenic effects [ 232 ]. ECFCs were engineered with a lentivirus encoding for murine integrin β1 and injected, either locally or intravenously, in a murine model of hindlimb ischemia [ 230 ].…”
Section: Genetic Manipulation Of Pro-angiogenic Signaling Pathwaysmentioning
confidence: 99%
“…ECFCs are emerging as suitable candidates for cell‐based therapy of ischemic diseases by virtue of their ability to paracrinally stimulate local angiogenesis and preserve cardiomyocyte viability and to physically engraft within nascent vasculature (Watt et al, ; Yoder, ). Accordingly, both PB‐ and UCB‐derived ECFCs may cause de novo vessel formation and functional recovery of blood flow in several rodent models of hindlimb ischemia (Flex et al, ; Goto et al, ; Kang, Coggins, Xiao, Rosenzweig, & Bischoff, ; Patel et al, ). A recent study further showed that VEGFR‐2 (KDR/Flk‐1), the receptor isoform that mediates the pro‐angiogenic effects of VEGF on EPCs (Moccia, Dragoni, et al, ; Rabbany, Heissig, Hattori, & Rafii, ), is also key to ECFCs‐dependent revascularization (Joo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, to establish whether MFSD2A overexpression on endothelial cells could promote in vivo the resolution of intestinal inflammation, we choose the Dextran Sodium Sulfate (DSS)-induced model of acute colitis. Moreover, we took advantage of the capability of human endothelial colony-forming cells (ECFCs), to be recruited to ischemic or inflamed tissues 27 , where they remodel the vascular compartment 28 . We transduced mCherry-tagged human ECFCs with MFSD2A-GFP-carrying lentiviral particles (ECFCs-MFSD2A) or GFP-expressing ECFCs (ECFCs-GFP), as control.…”
mentioning
confidence: 99%